2022
DOI: 10.1038/s43247-022-00615-2
|View full text |Cite
|
Sign up to set email alerts
|

A chemical threshold controls nanocrystallization and degassing behaviour in basalt magmas

Abstract: An increasing number of studies are being presented demonstrating that volcanic glasses can be heterogeneous at the nanoscale. These nano-heterogeneities can develop both during viscosity measurements in the laboratory and during magma eruptions. Our multifaceted study identifies here total transition metal oxide content as a crucial compositional factor governing the tendency of basalt melts and glasses towards nanolitization: at both anhydrous and hydrous conditions, an undercooled trachybasalt melt from Mt.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 199 publications
7
30
0
Order By: Relevance
“…and Tpeak; when such deviations were observed, Raman spectra were acquired to document that the sample changed during the measurement (i.e., crystallization and/or degassing). We indeed demonstrated in several recent works that Raman spectroscopy can reveal the precipitation of nanosized Fe-Ti-oxides (as expected during calorimetric measurements of magmatic melts at deep undercooling, where transition metals are poorly soluble and homogeneous crystal nucleation prevails over crystal growth), with sensitivity extending even to the early stages of amorphous phase separation anticipating the occurrence of actual crystals (Di Genova et al, 2020b, 2020a, 2017a, 2017bScarani et al, 2022;Zandona et al, 2022Zandona et al, , 2021Zandona et al, , 2019. Using this approach, we concluded that sample S38F5W1 may be reliably measured for qh ranging between 100 and 30000 K s -1 (see the expected linear dependence on qh in Figure 6); we obtained Tonset = 1055 ± 3 K and Tpeak = 1090 ± 1 K at qh = 1000 K s -1 .…”
Section: (Flash) Calorimetrysupporting
confidence: 69%
See 4 more Smart Citations
“…and Tpeak; when such deviations were observed, Raman spectra were acquired to document that the sample changed during the measurement (i.e., crystallization and/or degassing). We indeed demonstrated in several recent works that Raman spectroscopy can reveal the precipitation of nanosized Fe-Ti-oxides (as expected during calorimetric measurements of magmatic melts at deep undercooling, where transition metals are poorly soluble and homogeneous crystal nucleation prevails over crystal growth), with sensitivity extending even to the early stages of amorphous phase separation anticipating the occurrence of actual crystals (Di Genova et al, 2020b, 2020a, 2017a, 2017bScarani et al, 2022;Zandona et al, 2022Zandona et al, , 2021Zandona et al, , 2019. Using this approach, we concluded that sample S38F5W1 may be reliably measured for qh ranging between 100 and 30000 K s -1 (see the expected linear dependence on qh in Figure 6); we obtained Tonset = 1055 ± 3 K and Tpeak = 1090 ± 1 K at qh = 1000 K s -1 .…”
Section: (Flash) Calorimetrysupporting
confidence: 69%
“…The experimental procedure applied in this work has been presented, tested and optimized in previous studies (Cassetta et al, 2021;Di Genova et al, 2020b;Scarani et al, 2022;Stabile et al, 2021); its cornerstones are briefly summarized here. We have demonstrated that the combination of calorimetry (DSC) and Brillouin spectroscopy (BLS) enables the modelling of melt viscosity as a function of temperature [η(T)] (Cassetta et al, 2021).…”
Section: Deriving and Modelling Melt Viscositymentioning
confidence: 99%
See 3 more Smart Citations